Polymer nanocomposite film for dual colorimetric and fluorescent ascorbic acid detection integrated single-cell bioimaging with droplet microfluidic platform. (February 2020) - Alizadeh, Negar; Ghasemi, Foad; Salimi, Abdollah; Hallaj, Rahman; Fathi, Fardin; Soleimani, Farzad
Abstract: As one of the most important vitamins, which, participates in various physiological reactions in human body, Ascorbic Acid (AA) detected directly through fluorescent and colorimetric method. Our sensing system was based on the non-oxidation reduction strategy using fluorescent polymer nanocomposite (quantum yield: 26%) as a novel probe. The addition of AA can intensively suppress the fluorescence of the polymer nanocomposite through the static quenching effect (SQE). The linear response range of AA was obtained from 1 to 575 μM with LOD of 250 nM at a signal-to-noise ratio of 3. Additionally, the color of the nanoprobe was turned from purple to colorless, and a visual colorimetric assay has been also developed for the detection of AA. The absorbance at 604 nm is linearly related to the logarithm of the AA concentration in the range of 50–425 μM with LOD of 10 μM. More importantly, we have developed a droplet microfluidic approach for intracellular imaging of AA in living cells. Isolated small microdroplet allows the fast detection and imaging of AA in single cells. The current strategy provides an effective platform for monitoring and imaging biomolecules in living cells and could be extended to more broadly in cell biology. Highlights: PNF were successfully synthesized from thionine and potassium oxalate via sonication treatment. The fluorescence of PNF were quenched by ascorbic acid through SQE mechanism. Non-redox fluorescence strategy could effectively avoid the interference of the reducing substances and did not require the complex modification. Relative to the reported methods, the proposed method is much simpler and faster, a whole detection just needs 4 min. PNF with low cytotoxicity was used for single-cell imaging of AA, using droplet microfluidic platform.